The Influence of Leadership Style and Work Discipline on Employee Performance at Holiday Inn Resort Baruna Bali - Made Melysa Dwi Prastyawati; I Ketut Johny Pramanda Putra; Ida Bagus Agung Dharmanegara (PT Keberlanjutan Strategis Indonesia, 2026)
The increasingly competitive growth of the hospitality industry requires organizations to manage their human resources effectively in order to achieve organizational goals. Employee performance is a crucial factor that determines an organization's success in delivering high-quality services and maintaining its competitive advantage. However, based on preliminary observations at Holiday Inn Resort Baruna Bali, indications of suboptimal employee performance were still identified, which are presumed to be influenced by leadership style and work discipline. This study aims to determine the effect of leadership style and work discipline, on employee performance. The population in this study consists of employees of Holiday Inn Resort Baruna Bali, with a sample of 133 respondents. The research method used is quantitative. Data analysis techniques include validity test, reliability test, classical assumption test, multiple linear regression analysis, F-test, and t-test using SPSS version 26. The results of the study indicate that leadership style and work discipline have a positive and significant effect on employee performance. Partially, leadership style has a positive and significant effect on employee performance, and work discipline also has a positive and significant effect on employee performance.